Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1002/1097-0274(200102)39:2<171::aid-ajim1004>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

A case‐crossover study of occupational traumatic hand injury: Methods and initial findings

Abstract: Background Acute hand injury is the leading cause of occupational injury treated in United States' hospital emergency departments (e.g., laceration, crush or fracture). To identify risk factors for traumatic hand injuries, we conducted a case-crossover study of transient exposures (e.g., being rushed) for acute occupational traumatic hand injury. Methods The case-crossover method, which uses subjects as their own controls, was used to identify risk factors for occupational hand injury. Two hundred and thirty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 4 publications
3
59
1
1
Order By: Relevance
“…We previously reported on the development of our structured questionnaire (15), modeled after the studies by Sorock et al (11), translated into Chinese, and evaluated in the previous pilot study (13). The questionnaire recorded information on 8 self-reported transient expo- Jin et al sures starting at 90 minutes before the onset of the hand injury regarding the participant's work equipment, work practices, and worker-and workplace-related factors.…”
Section: Data Collectionsupporting
confidence: 90%
See 4 more Smart Citations
“…We previously reported on the development of our structured questionnaire (15), modeled after the studies by Sorock et al (11), translated into Chinese, and evaluated in the previous pilot study (13). The questionnaire recorded information on 8 self-reported transient expo- Jin et al sures starting at 90 minutes before the onset of the hand injury regarding the participant's work equipment, work practices, and worker-and workplace-related factors.…”
Section: Data Collectionsupporting
confidence: 90%
“…We utilized the case-crossover design to assess if the injury may have been "triggered" by one or more transient risk factors that occurred just prior to the injury. The same protocol was used as in a North American study by Sorock et al (11) and Lombardi et al (9) and in Hong Kong, China, by Chow et al (12). In these prior studies, wearing gloves was identified as a protective factor that was significant in Sorock et al's report (11) (RR 0.4, 95% CI 0.3-0.8) but insignificant in Chow et al's (RR 0.7, 95% CI 0.38-1.34).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations